Contact dermatitis from shoes: an update - Dadlani Ramchandani, Noor Mahesh (Revista Internacional de Ciencias Podológicas, 2016)
Contact dermatitis is a common inflammatory skin condition characterized by erythematous and pruritic skin lesions that occur after contact with a foreign substance. There are two forms of contact dermatitis: irritant and allergic. Irritant contact dermatitis is caused by the non–immune-modulated irritation of the skin by a substance, leading to skin changes. Allergic contact dermatitis is a delayed hypersensitivity reaction in which a foreign substance comes into contact with the skin; skin changes occur after reexposure to the substance. A medical condition referred to as “shoe dermatitis” is a form of contact dermatitis caused by the contact of the foot with parts of the shoe due to these materials. Shoe dermatitis is a diagnostic and therapeutic challenge and is a common type of contact dermatitis. It is imperative the foot and ankle physician become familiar with recognizing signs and symptoms of shoe dermatitis so that their patients can be accurately diagnosis and appropriately treated to avoid secondary infections and disability. This review will first present causative factors for the etiology of shoe contact dermatitis supported by clinical-based evidence as found in the medical literature. Secondly, a description of the signs and symptoms of shoe contact dermatitis will be presented in a narrative fashion. Finally, both treatment options and preventative measures to avoid shoe.